2018
DOI: 10.1111/ppe.12512
|View full text |Cite|
|
Sign up to set email alerts
|

Good practices for the design, analysis, and interpretation of observational studies on birth spacing and perinatal health outcomes

Abstract: Background Meta‐analyses of observational studies have shown that women with a shorter interpregnancy interval (the time from delivery to start of a subsequent pregnancy) are more likely to experience adverse pregnancy outcomes, such as preterm delivery or small for gestational age birth, than women who space their births further apart. However, the studies used to inform these estimates have methodological shortcomings. Methods In this commentary, we summarise the disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 59 publications
1
85
0
Order By: Relevance
“…Internal validity was determined by evaluating sources of potential information bias (misclassification), confounding and selection bias. Assessments were guided by the key study design considerations identified by a recent Office of Population Affairs’ expert work group reviewing the evidence on short birth spacing and adverse pregnancy outcomes . These included the extent to which the study incorporated a detailed measure of socio‐economic position, accounted for pregnancy intention, identified early pregnancy losses occurring between the last birth and the subsequent pregnancy being evaluated (which could result in differential misclassification of interpregnancy interval) and accounted for perinatal death (stillbirth or neonatal death) in the previous pregnancy …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Internal validity was determined by evaluating sources of potential information bias (misclassification), confounding and selection bias. Assessments were guided by the key study design considerations identified by a recent Office of Population Affairs’ expert work group reviewing the evidence on short birth spacing and adverse pregnancy outcomes . These included the extent to which the study incorporated a detailed measure of socio‐economic position, accounted for pregnancy intention, identified early pregnancy losses occurring between the last birth and the subsequent pregnancy being evaluated (which could result in differential misclassification of interpregnancy interval) and accounted for perinatal death (stillbirth or neonatal death) in the previous pregnancy …”
Section: Methodsmentioning
confidence: 99%
“…and adverse pregnancy outcomes. 44 These included the extent to which the study incorporated a detailed measure of socioeconomic position, accounted for pregnancy intention, identified early pregnancy losses occurring between the last birth and the subsequent pregnancy being evaluated (which could result in differential misclassification of interpregnancy interval) and accounted for perinatal death (stillbirth or neonatal death) in the previous pregnancy. 44 External validity (generalisability) was determined by comparing the study population to either the general obstetric population in the United States or, for studies of women with specific obstetric history, a population with similar history in the United States.…”
Section: Data Abstraction Study Quality Assessment Data Synthesismentioning
confidence: 99%
“…What follows below are summaries of five key issues identified by the expert work group members. More information on good practices when conducting analyses of short interpregnancy interval on adverse pregnancy outcomes using observational study data is detailed elsewhere in this journal supplement …”
Section: Methodological Limitations Of Studiesmentioning
confidence: 99%
“…While researchers should plan their analysis according to their specific research question, consistent definitions of interpregnancy interval are essential to combining study results. Presenting results using standardised cut‐points and reference groups for categorical analyses of interpregnancy intervals and consistent definitions of commonly examined outcomes would improve the research base . Further, providing a complete description of the interpregnancy interval, such as whether or not intervening pregnancy losses are included in the interval, would aid in causal interpretation of the study's estimates.…”
Section: Methodological Limitations Of Studiesmentioning
confidence: 99%
“…The first paper is a summary of the meeting proceedings, including a discussion of the strength of the evidence for the causal effect of short interpregnancy intervals on adverse perinatal and maternal health outcomes and priorities for future work. The second paper discusses good practices for the future design, analysis, and interpretation of observational studies on interpregnancy intervals and adverse pregnancy outcomes identified by experts at the meeting . The supplement also includes two updated systematic reviews on short interpregnancy interval and perinatal and maternal health outcomes in high‐income settings; preliminary results from these systematic reviews were presented at the meeting and are briefly summarised in the meeting proceedings .…”
Section: Contributions Of the Manuscripts Contained In This Supplementmentioning
confidence: 99%